Effect of Organizational Commitment and Employee Engagement on Organizational Change through Voice Behaviour - Zacharias, Tehubijuluw (Budapest International Research and Critics University, 2022)
This study aims to analyze the influence of organizational commitment culture and employee engagement either directly or indirectly on organizational change through the voice behavior of Regional Financial and Asset Management Agency (BPKAD) Central Maluku Regency employees. The research was conducted at Regional Financial and Asset Management Agency (BPKAD) Central Maluku Regency for 2 (two) months, from March to April 2022. The population used in this study were all employees of the Regional Financial and Asset Management Agency (BPKAD) of Central Maluku Regency as many as 60 people. The method of determining the sample is full sampling. The results of the study conclude that (1) organizational commitment has a positive and significant effect on employee voice behavior, (2) employee engagement has a positive and significant effect on employee voice behavior, (3) voice behavior has a positive and significant effect on organizational change, (4) organizational commitment positive and significant effect on organizational change, (5) employee engagement has a positive and significant effect on organizational change, (6) organizational commitment has a positive and significant effect on organizational change through employee voice behavior, (7) employee engagement has a positive and significant effect on organizational change through employee voice behavior.